Risk, Regulation, and Reach: A Critical Analysis of Emerging Issues in the Indian Insurance Industry - Bathia, Amit (International Insurance Law Review, 2025)
The Indian insurance sector is undergoing profound transformation driven by technological advancement, regulatory reform, and evolving risk paradigms. This study, titled “Risk, Regulation, and Reach: A Critical Analysis of Emerging Issues in the Indian Insurance Industry,” explores the intersection of rising systemic and climate-related risks, regulatory modernization initiatives—such as digitization, consumer protection, and solvency norms—and efforts to expand insurance penetration across socio-economic strata. We critically examine how emerging risks challenge conventional actuarial frameworks, assess how regulatory bodies are adapting via innovation and tighter oversight, and analyze strategies for improving the reach of insurance products among underinsured populations. Drawing on recent datasets, regulatory releases, and academic studies, our findings reveal the need for dynamic regulatory frameworks balancing stability and innovation, and suggest policy interventions that can help the sector achieve inclusive resilience.
ISME
Keywords: Risk; Regulation; Reach; Indian Insurance; Emerging Issues; Insurance Penetration